1983
DOI: 10.1007/bf00663909
|View full text |Cite
|
Sign up to set email alerts
|

Overall open-loop gain of rapidly acting arterial pressure control system in rabbits

Abstract: We estimated the overall open-loop gain of the rapidly acting arterial pressure control system without surgically or pharmacologically opening the reflex loop in rabbits. Animals anesthetized by intravenous injection of Nembutal (27.5 mg X kg-1 body weight) and heparinized were bled by 2 ml X kg-1 body weight within 1-2 s through a catheter inserted into the aortic arch. Arterial pressure change after the quick mild hemorrhage was monitored via a catheter placed in the right subclavian artery for more than 2 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1984
1984
1991
1991

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Thus, the effect of pentobarbital anesthesia on the baroreflex system is still in dispute. HosoMI et al (1983) reported the G value (7.3) estimated from arterial pressure response to quick mild hemorrhage from the aorta in anesthetized rabbits. This value is within the range of the G value (7.1±0.3) estimated in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the effect of pentobarbital anesthesia on the baroreflex system is still in dispute. HosoMI et al (1983) reported the G value (7.3) estimated from arterial pressure response to quick mild hemorrhage from the aorta in anesthetized rabbits. This value is within the range of the G value (7.1±0.3) estimated in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…This quick mild hemorrhage caused a rapid fall in the systemic arterial pressure and then activated the rapidly acting arterial pressure control system, i.e., the vagally mediated baroreflex system in this protocol, which restored the systemic arterial pressure to the control level and minimized the systemic arterial pressure fall. We could estimate the open-loop gain (Gv) of the vagally mediated baroreflex system from the systemic arterial pressure change as described previously (HOsOMI et al, 1983). Briefly, we sampled the control mean arterial pressure (CMAP) just before the hemorrhage and then the immediate fall in mean arterial pressure (dAPI) from the control mean arterial pressure at completion of the hemorrhage.…”
Section: Methodsmentioning
confidence: 99%